Visionary Leadership of a Kiai in Pesantren Based Educational Transformation: A Case Study at Pondok Pesantren Amanatul Ummah - Ainur Rofiq; Moh. Ainul Yaqin (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2026)
This study analyzes the visionary leadership of KH Asep Saifuddin Chalim, founder and leader (pengasuh) of Pondok Pesantren Amanatul Ummah, as expressed across four dimensions of Burt Nanus's visionary leadership model: direction setter, agent of change, spokesperson, and coach. A qualitative phenomenological design was employed. Data were collected at two research sites Desa Kembangbelor, Kecamatan Pacet, Kabupaten Mojokerto, and Siwalankerto, Surabaya through in-depth semi-structured interviews with twelve key informants comprising KH Asep Saifuddin Chalim (main informant), three school principals at different educational levels, five senior teachers, and three administrative officers. Findings were triangulated through participant observation and analysis of institutional documents. Phenomenological analysis revealed that KH Asep Saifuddin Chalim enacts visionary leadership through: (1) a clearly articulated and communicated institutional vision izzul Islam wal muslimin rahmatan lil 'alamin operationalized into a structured educational system spanning secondary school through university; (2) transformational institutional change that has grown Amanatul Ummah from fewer than 50 santri in its founding years to over 4,000, with alumni securing placements in leading domestic universities and international institutions in Egypt, Yemen, Morocco, and elsewhere; (3) extensive national spokesperson activity through PERGUNU central board membership and professorial appointment at UIN Sunan Ampel Surabaya; and (4) a distinctive coaching approach integrating spiritual exemplarity with professional accountability. The study contributes a Spiritual-Visionary Leadership model that synthesizes Islamic educational values with systematic institutional management, proposing that the effectiveness of kiai leadership depends on the deliberate institutionalization of vision beyond the person of the leader.